Postcolonial powers of opposition in Octavia Butler’s Kindred - Al Ogaili, Thamer Amer Jubouri; Babaee, Ruzbeh (Australian International Academic Centre, 2016)
This study will examine postcolonial powers of opposition in Octavia Butler’s Kindred (1979); through Homi Bhabha’s concept of ambivalence and Edward Said’s self-other relationship. By using these concepts, this research aims to unravel how the colonized and the colonizer perceive each in the selected works. It will offer an in-depth analysis of the thematic and ideological characteristics of selected works. Thus, the focus will mainly be on the theme of the mutual relationship between the colonized and the colonizer in the selected works. This relationship is specified to the concept of ambivalence. This concept incarnates the dual, yet, uncontrolled relationship between the colonized and the colonizer. Nevertheless, the colonized considers the colonizer as oppressive but an envious power; and the colonizer judges the colonized as inferior but indigenous. The colonial relationship will also be revealed by using the concept of self-other. Such concept scrutinizes the way the colonized and the colonizer perceive and resist each other. Accordingly, the research’s main focus point is the power relationship developed in the light of colonial ambivalence and self-other continuum. The research’s methodology relies on Bhabha’s concept of ambivalence and Edward Said’s self-other relationship. In The Location of Culture (1994), Bhabha maintains that the concept of ambivalence conveys “the exercise of colonialist authority, however, requires the production of differentiations, individuations, identity effects through which discriminatory practices can map out subject populations that are tarred with the visible and transparent mark of power” (111). Edward Said, in his discussion of self-other relationship in Orientalism (1979), argues that self-other relationship is “the vacillation [inconstancy] between the familiar [self] and the alien [other]” (72).